Effects of concurrent task on gait and postural control performance in children with traumatic brain injury / Rabiatul Adawiah Abdul Rahman - Abdul Rahman, Rabiatul Adawiah (2018)
Children with traumatic brain injury (TBI) have a wide range of cognitive and functional mobility impairment. Concurrent task refers to the secondary tasks that are performed simultaneously with the primary task (walking and standing). Walking and postural control under concurrent tasks may require greater attentional resource which could adversely affect their performance. Improper gait and postural control pattern during walking while performing concurrent task may contribute to fall in this population. Objectives: Thus, the purpose of this study was (1) to compare the effect of concurrent task on temporal-spatial gait parameters, (2) to compare the effect of concurrent task on postural control performance, and (3) to identify the dual-task cost (DTC) on gait parameters between TBI and typically developing (TD) children. Methods: Sixteen children with TBI (mean age 11.63 ± 1.89 years) and 22 TD controls (mean age 11.41 ± 2.24 years) participated in this case-control study design. Each participant performed straight walking and upright standing under three different conditions: single, concurrent motor, and concurrent cognitive task. Gait parameters included gait velocity, stride length, stride time, cadence, and double support time. While postural control performance measure includes sway area, anterior-posterior (AP) sway velocity, medio-lateral (ML) sway velocity, AP sway distance and ML sway distance. These parameters and performances were measured using the APDM® Mobility Lab. In addition, DTC for each gait parameter was calculated using specific formula. A descriptive analysis and repeated-measure analysis of variance (ANOVA) were used to analyze the data. Results: Children with TBI showed more significant deterioration in gait performance than TD children (p< 0.05). Concurrent tasks (motor and cognitive) significantly decreased gait velocity and cadence, while stride time increased and differences were more discerned under concurrent cognitive task. Similar to postural control performance, children with TBI showed more significant decrement than TD children (p< 0.05). Both concurrent tasks (motor and cognitive) significantly decreased postural control performance in both groups with more pronounced changes in children with TBI than TD controls. As for DTC, children with TBI had higher negative DTC in all gait parameters compared to TD control which indicated case group had more interference and deterioration of walking performance under concurrent task conditions. Both concurrent tasks (motor and cognitive) led to the deterioration of walking performance in all parameters evidenced by negative DTC in both groups. Conclusion: The findings of this study demonstrated performing concurrent tasks (motor and cognitive) while walking and upright standing resulted in deterioration of both performance. Both gait and postural control performance may be affected by task complexity following TBI. The existence of cognitive and balance impairment in children with TBI will possibly cause concurrent tasks to be more complex and demands greater attention compared to a single task. This study also has clinical implications for assessment and rehabilitation in children with TBI. The ability to execute concurrent tasks in this population is crucial to ensure safety during walking and postural control, especially in outdoor settings. Thus, it is recommended that routine rehabilitation intervention for children with TBI should incorporate concurrent task for gait and postural control to augment and achieve optimal functional performance.